Intuitionistic Fuzzy Left and Right Bi-Quasi Ideals of Semirings. Issue 1 (January 2021) - Murugadas, P.; Amala, R.
Abstract: In this article, the notion of intuitionistic fuzzy bi-quasi ideal of semiring has been explored and some results using regularity concept are analyzed.